Choking under pressure in front of a supportive audience: Evidence from professional biathlon - Harb-Wu, K.; Krumer, A. (Discussion Paper no. 2017-17, 2017)
Performing in front of a supportive audience increases motivation. However, it also creates a psychological pressure, which may impair performance, especially in precision tasks. In this paper we exploit a unique setting in which professionals compete in a real-life contest with high monetary rewards in order to assess how they respond to the presence of a supportive audience. Using the task of shooting in sprint competitions of professional biathlon events over the period of sixteen years, our fixed effects estimations show that high-profile biathletes miss significantly more shots when competing in front of a supportive audience. Our results are in line with the hypothesis that a friendly environment induces individuals to choke when performing skill-based tasks.